Given:
Foci of the hyperbola = (-3,3), (-3, 9)
Vertices of the hyperbola = (-3, 4), (-3, 8)
Required: Equation of the hyperbola
Step-by-step explanation:
The x-coordinates of the vertices and foci are same, so the transverse axis is parallel to the y-axis. Thus, the equation of the hyperbola will have the form
![((y-k)^2)/(a^2)-((x-h)^2)/(b^2)=1](https://img.qammunity.org/2023/formulas/mathematics/college/s1kgne2fewzyluu89sxmu2wqu6dp2foc21.png)
First, identify the center (h, k). The center is halfway between the vertices (-3, 4) and (-3, 8). Apply the midpoint formula.
![\begin{gathered} (h,k)=((-3+-3)/(2),(4+8)/(2)) \\ =(-3,6) \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/g9lawv44lhfkilypy96yrsulftnqf9yomk.png)
Next, find the square of a.
The length of the transverse axis is, 2a, bounded by the vertices. So, to find the square of a, determine the distance between the y-coordinates of the vertices.
![\begin{gathered} 2a=|4-8| \\ 2a=4 \\ a=(4)/(2)=2 \\ a^2=2^2=4 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/aji1covxyz3nmqrldm4i60g895kqwzb9lv.png)
Find the square of c. The coordinates of the foci are (h, k+c) and (h, k-c). So (h, k- c) = (-3, 3) and (h, k+c) = (-3, 9). Use the y-coordinate from either of these points to solve for c. Using the point (-3, 3) and substituting k = 6.
![\begin{gathered} k+c=9 \\ 6+c=9 \\ c=9-6 \\ =3 \\ c^2=3^2=9 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/czkj877td9s7d6umk2drxp69fxgbnzrjte.png)
Solve for square of b using the equation
![b^2=c^2-a^2](https://img.qammunity.org/2023/formulas/mathematics/high-school/5cw06zwjh1szoeepv4ywr3m2sldt68z3j0.png)
Substitute the obtained values.
![\begin{gathered} b^2=9-4 \\ =5 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/rdfi5ypgvvxyuwuwn8btdwmj4mjol0rm5l.png)
Finally, substitute the obtained values into the standard form of the equation
![\begin{gathered} ((y-6)^2)/(4)-((x-(-3))^2)/(9)=1 \\ ((y-6)^(2))/(4)-((x+3)^2)/(9)=1 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/ji6klo7wmhco4afefb8tubhuhoae68q6i0.png)
Final Answer: The equation of the required hyperbola is
![((y-6)^2)/(4)-((x+3)^2)/(9)=1](https://img.qammunity.org/2023/formulas/mathematics/college/zo8y5uqrh602l6kg4szx7s23c9rpethokh.png)